Molecular consequences of the SERPINH1/HSP47 mutation in the dachshund natural model of osteogenesis imperfecta - Lindert, Uschi; Haußer-Siller, Ingrid (The journal of biological chemistry, 2015)
Background: The collagen chaperone HSP47 is implicated in recessive osteogenesis imperfecta (OI)., Results: In OI dachshunds, an HSP47(L326P) mutation affects the post-translational modification, secretion, and cross-linking of collagen type I., Conclusion: Impaired chaperone function, ER stress, and aberrant bone collagen cross-linking are implicated in the disease mechanism., Significance: Our findings are relevant for the diagnosis and pathological understanding of OI caused by an HSP47 defect., Osteogenesis imperfecta (OI) is a heritable connective tissue disease characterized by bone fragility and increased risk of fractures. Up to now, mutations in at least 18 genes have been associated with dominant and recessive forms of OI that affect the production or post-translational processing of procollagen or alter bone homeostasis. Among those, SERPINH1 encoding heat shock protein 47 (HSP47), a chaperone exclusive for collagen folding in the ER, was identified to cause a severe form of OI in dachshunds (L326P) as well as in humans (one single case with a L78P mutation). To elucidate the disease mechanism underlying OI in the dog model, we applied a range of biochemical assays to mutant and control skin fibroblasts as well as on bone samples. These experiments revealed that type I collagen synthesized by mutant cells had decreased electrophoretic mobility. Procollagen was retained intracellularly with concomitant dilation of ER cisternae and activation of the ER stress response markers GRP78 and phospho-eIF2α, thus suggesting a defect in procollagen processing. In line with the migration shift detected on SDS-PAGE of cell culture collagen, extracts of bone collagen from the OI dog showed a similar mobility shift, and on tandem mass spectrometry, the chains were post-translationally overmodified. The bone collagen had a higher content of pyridinoline than control dog bone. We conclude that the SERPINH1 mutation in this naturally occurring model of OI impairs how HSP47 acts as a chaperone in the ER. This results in abnormal post-translational modification and cross-linking of the bone collagen.